Snack Bar Tepung Sorgum dan Tepung Kelapa sebagai Pangan Fungsional untuk Penderita Diabetes Melitus Tipe 2: Sorghum Flour and Coconut Flour Snack Bars as Functional Foods for Type 2 Diabetes Mellitus - Zahra, Raisa Siti; Fauziyah, A'immatul; Ilmi, Ibnu Malkan Bakhrul (Amerta Nutrition, 2025)
Background: People with type 2 diabetes mellitus (T2DM) can control blood sugar levels through adequate fiber consumption. Sorghum flour and coconut flour are non-gluten flours that have high fiber content. Developing functional foods, such as snack bars made from these flours, could help regulate blood glucose levels. Objectives: This study aimed to examine the effect of the proportion of sorghum flour and coconut flour on the nutritional content, dietary fiber content, and organoleptic properties of snack bars. Methods: This study used a completely randomized design with 3 formulations (70:30, 50:50, and 30:70 ratios of sorghum to coconut flour) and 2 repetitions. The gravimetric method was used to analyze water content and ash content. The Kjeldahl and Soxhlet extraction methods were employed to analyze the protein and fat content, respectively. Carbohydrate content was determined using by difference method, and fiber content was evaluated using the enzymatic method. ANOVA and the Kruskal-Wallis test were used to see the differences in proximate, fiber, and organoleptic properties, respectively. Results: The results showed significant differences in ash content (p-value<0.001), protein (p-value=0.002), fat (p-value=0.047), carbohydrates (p-value=0.049), and dietary fiber (p-value<0.001). Taste is one of the hedonic test parameters that has a significant difference (p-value=0.005). The selected snack bar formula was F3 with energy, fat, protein, carbohydrate, and fiber content was 108 kcal, 5.18 g, 4.56 g, 10.85 g, and 10.91 g respectively. Conclusions: Snack bars made from sorghum and coconut flour are rich in dietary fiber and suitable for consumption by individuals with T2DM.